2014
DOI: 10.1007/978-1-4471-6458-6_13
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Gene Transfer for Cancer Gene Therapy

Abstract: Gene therapy vectors are among the treatments currently used to treat malignant tumors. Gene therapy vectors use a specific therapeutic transgene that causes death in cancer cells. In early attempts at gene therapy, therapeutic transgenes were driven by nonspecific vectors which induced toxicity to normal cells in addition to the cancer cells. Recently, novel cancer specific viral vectors have been developed that target cancer cells leaving normal cells unharmed. Here we review such cancer specific gene therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 120 publications
(123 reference statements)
0
5
0
Order By: Relevance
“…In clinical practice, we often need combined application of a number of different drugs to affect the tumor growth [ 154 ]. On the other hand, gene therapy technology can inhibit the expression of drug resistance gene mRNA, with a broad clinical application prospects [ 155 , 156 ]. As the researchers on the tumor resistance mechanism continuously deepening and related treatment technology continuously develop, human can improve the effect of clinical chemotherapy, reverse the resistance of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, we often need combined application of a number of different drugs to affect the tumor growth [ 154 ]. On the other hand, gene therapy technology can inhibit the expression of drug resistance gene mRNA, with a broad clinical application prospects [ 155 , 156 ]. As the researchers on the tumor resistance mechanism continuously deepening and related treatment technology continuously develop, human can improve the effect of clinical chemotherapy, reverse the resistance of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A number of different vectors are currently being used for gene therapy of malignant tumors. Whereas early vectors were non-specific, novel vectors, especially viruses, have been developed that target cancer cells but leave normal cells unharmed ( 27 ). We have reported that attenuated Salmonella typhimurium has potential utility for transgene delivery, since it shows >1,000-fold preferential accumulation in tumors compared with normal tissues ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be anticipated from the outset of vector development, particularly when utilizing known cytotoxic transgenes, for example, in cancer-killing vectors1029 or anti-HIV-1 genes that encode restriction factors that affect retroviral vectors, for example, APOBEC3G (ref. 30) and TRIMcyp (ref.…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary gene therapy vectors based on RNA viruses such as γ-Retroviruses and Lentiviruses12, and DNA viruses such as Adenovirus3 and Adeno-associated virus (AAV)4 have shown promise in a growing number of human disease indications. These include ex vivo modification of patient cells for hematological conditions56, and in vivo treatment of ophthalmic7, cardiovascular8, neurodegenerative diseases9 and tumour therapy10. Immunogen-encoding vectors based on Poxviruses11 and Avian viruses12 are widely used in human and animal vaccinations.…”
mentioning
confidence: 99%